(untitled) (Mustansiria Dental Journal, 2018)
Diabetes mellitus (DM) is a systemic disease with several major complications. One of the important complications of diabetes mellitus is periodontal disease. The risk for this complication is not equal in all DM patients and thus some factors may increase its severity. To study the relationship between selected clinical characteristics and periodontal disease in type 2 (DM) patients. Two hundred and four type 2 diabetic patients were enrolled in this study; their ages were (28-71) years. The clinical characteristics included age, sex, body mass index (BMI), duration of (DM), smoking, and history of important diseases that complicate (DM) including hypertension, coronary heart disease, and arthritis. Periodontal status was evaluated by periodontal disease index (PDI) which included plaque, calculus, and periodontal components of this index. The means of plaque, calculus, and periodontal disease index were compared between patients who were grouped according to the presence or absence of the selected clinical characteristics. There was a significant difference in mean value of calculus index between hypertensive and non hypertensive patients (0.56±0.53 vs. 0.72±0.43, P< 0.05). Also there was a significant difference in periodontal disease index between hypertensive diabetic patient compared to diabetic patients who had no hypertension (3.84±0.75 vs. 3.2±0.99, P<0.001). Analysis of correlation showed that the correlations between plaque index and both calculus index and periodontal disease index were highly significant (P<0.001). The correlation was positive and highly significant between PDI and age (P<0.001) while it was significant between PDI and duration of DM ( P < 0.05 ). Hypertension seems to have a role in aggravating periodontitis in type 2 DM particularly with increasing age and duration of disease. Preventive periodontal disease programs should take in consideration presence of hypertension in type 2 DM.